MENYONGSONG KEBIJAKAN PENDIDIKAN MENENGAH UNIVERSAL: PEMBELAJARAN DARI IMPLEMENTASI WAJAR DIKDAS 9 TAHUN - Titik Handayani (Research Centre for Population, Indonesian Institute of Sciences, 2012)
The Universal Secondary Education policy or the 12-Year Compulsory Education Policy has been declared by the central government to be implemented in 2013, and followed by the regions at the provincial and regency levels. In fact, there are some areas that have been declared in advance, including the DKI - Jakarta, where the 12-year Compulsory Education Policy started this new academic year. As the sustainability of the 9-Year Compulsory Basic Education program has had many problems in its implementation, the 12 Year Compulsory Education Policy will also face many obstacles. Moreover, this policy does not have a foundation or basis in law as a reference for the implementation of the program. In contrast, the 9 Year Compulsory BasicEducation Program is a mandate of the Act. Considering the importance of this policy, the legal foundation at the national level at least in the form of local regulations, should belaid immediately.. This paper aims to analyze various issues related to the policy of the9 Year Basic Education Program at the level of concepts, indicators - achievement of targets and implementation. Various problems can showwhat can be used to implement the program for 12 Years. Data sources made use of were secondary data from the Ministry of Education and Culture as well as the results of research conducted by the Research Center for Population, Indonesian Institute of Sciences (PPK-LIPI) which was conducted from 2006 to 2011.Key Words: elementary and secondary education policy, compulsory education and the quality of human resources